2019
DOI: 10.1093/schbul/sbz043
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Reality Testing in Mice Through Dopamine-Dependent Associatively Evoked Processing of Absent Gustatory Stimuli

Abstract: Impairments in reality testing are core features of numerous neuropsychiatric conditions. However, relatively few animal models have been developed to assess this critical facet of neuropsychiatric illness, thus impeding our understanding of the underlying central systems and circuits. Using mice in which dominant-negative Disrupted-in-Schizophrenia-1 is expressed throughout central nervous system circuitry (DN-DISC1-PrP), the capacity for an auditory conditioned stimulus (CS) to evoke perceptual processing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 62 publications
3
21
0
Order By: Relevance
“…The same mice when treated with the antipsychotic risperidone showed both reduced hyperresponsiveness to amphetamine and an attenuated tendency for representation-mediated learning, suggesting that conditioned hallucinations as conceptualized here may be due, at least in part, to dopamine hyperfunction (Koh et al, 2018a). Further substantiating those findings, treatment with haloperidol, which exhibits high affinity dopamine D 2 receptor antagonism, also effectively reduced the tendency to evoke internal representations in DISC-1 transgenic mice (Fry et al, 2019). A role for dopaminergic function demonstrated in those studies is consistent with the view that internal representations elicited in the context of mediated learning approximates hallucinations in patients insofar that hallucinations have also shown some sensitivity to antipsychotics that target dopamine function, and that hallucinations might arise from a dysregulation of the dopamine system causing misattribution of salience to internal representations of percepts and memories (Kapur, 2003).…”
Section: Circuits and Network In Neurocognitive Functionsupporting
confidence: 68%
See 2 more Smart Citations
“…The same mice when treated with the antipsychotic risperidone showed both reduced hyperresponsiveness to amphetamine and an attenuated tendency for representation-mediated learning, suggesting that conditioned hallucinations as conceptualized here may be due, at least in part, to dopamine hyperfunction (Koh et al, 2018a). Further substantiating those findings, treatment with haloperidol, which exhibits high affinity dopamine D 2 receptor antagonism, also effectively reduced the tendency to evoke internal representations in DISC-1 transgenic mice (Fry et al, 2019). A role for dopaminergic function demonstrated in those studies is consistent with the view that internal representations elicited in the context of mediated learning approximates hallucinations in patients insofar that hallucinations have also shown some sensitivity to antipsychotics that target dopamine function, and that hallucinations might arise from a dysregulation of the dopamine system causing misattribution of salience to internal representations of percepts and memories (Kapur, 2003).…”
Section: Circuits and Network In Neurocognitive Functionsupporting
confidence: 68%
“…We found that the previously taste-associated odor induced a stronger neural activation in the insular taste cortex in mice exposed to ketamine during adolescence than control mice. Using DISC-1 transgenic mice, Fry et al, (2019) similarly found those mice to display a greater c-fos expression in the insular cortex in response to an auditory cue previously paired with a taste. Taken together with the behavioral studies, the neural activation data further strengthened the assertion that animals used to model symptoms of schizophrenia, which do not exhibit any general alteration in simple associative conditioning (Johnson et al, 2013;Koh et al, 2018, Fig.…”
Section: Neural Activation Of Internal Memory Representationmentioning
confidence: 95%
See 1 more Smart Citation
“…Based on the cognitive perspective described above, we and others have shown that mice used to model schizophrenia were more susceptible to psychosis-like behavior than normal animals as instantiated by a greater tendency to form associations between stimuli or events that were mediated by prior experience [2][3][4]. For example, using a well-established ketamine mouse model that is known to recapitulate many of the symptoms seen in schizophrenia [5,6], we used a representation-mediated learning paradigm to show that, when an odor and a taste are repeatedly paired, ketamine-exposed mice have an increased tendency to use the odor to evoke a putative inner representation of the taste that could enter into an association with illness [3].…”
Section: Dear Editormentioning
confidence: 99%
“…Interestingly, the reconceptualization of schizophrenia symptoms as aberrant perceptions (hallucinations) (Corlett et al, 2019) and beliefs (delusions) (Feeney et al, 2017), has provided the framework to be studied through associative learning tasks in both humans and animals (Powers et al, 2017;Dwyer, 2018;Koh and Gallagher, 2020). Indeed, impaired "reality testing" was recently demonstrated in several animal models of schizophrenia in a way that mimics psychotic-like percepts (McDannald et al, 2011;Kim and Koh, 2016;Busquets-Garcia et al, 2017;Koh et al, 2018;Fry et al, 2019), with recent evidence suggesting that such phenomena involve dopamine signaling (Schmack et al, 2021).…”
Section: Concluding Remarks: From Imagination To Psychosis?mentioning
confidence: 99%